Thermal modeling and experimental evaluation of five different photovoltaic modules integrated on prototype test cells with and without water flow. (1st June 2018) - Tomar, Vivek; Tiwari, G.N.; Bhatti, T.S.; Norton, Brian
Highlights: Thermal modelling for ηm and Tr of five different PV modules as BIPVT is presented. Analytical model is developed for ηm by surface water flow cooling. Test cells based experiments are performed for five different PV technologies. Constant temperature mode is attained by varying mass flow rate in test cell. Dynamic behaviour of five PVT technologies is monitored in outdoor condition. Abstract: An analytical model of temperature dependent electrical and thermal efficiency of mono-crystalline (m-Si), polycrystalline (p-Si), amorphous silicon thin film (a-Si), cadmium telluride thin film (CdTe) and copper indium gallium selenide (CIGS) photovoltaic modules integrated on five prototypes identical insulted test cells is developed with and without surface water flow. This model helps in ascertaining the influence of temperature on their performance of building integrated photovoltaic-thermal (BiPVT) system. The theoretically calculated results are experimentally validated in outdoor ambient environment. The electrical & thermal efficiencies are calculated for both high and low mass flow rate of water, m ̇ w . Daily average electrical efficiency of photovoltaic modules; m-Si, p-Si, a-Si, CdTe and CIGS with and without water flow are found to be 12.30%, 10.98%, 6.08%, 6.60% and 7.71%, and 11.41%, 10.30%, 5.86%, 6.26% and 6.99% respectively. In constant room temperature mode, variation in mass flow rate of water, m ̇ w is also evaluated. Overall thermal efficiency and overall exergy for all photovoltaic modules in both cases are also calculated. The characteristic equations of photovoltaic modules integrated on test cells are also developed for both cases.